Stable and Broad Multiwavelength Generation with the Assistance of Intensity Dependent Loss Mechanism based on Bidirectional SOA - Sulaiman A.H.; Ismail A.; Abdullah F.; Jamaludin M.Z.; Mahdi M.A. (IOP Publishing Ltd, 2023)
Fiber amplifiers; Fiber lasers; Microcomputers; Polarization; Bidirectional semiconductor optical amplifiers; High peak power; Intensity-dependent; Loss mechanisms; Multi wavelength fiber laser; Multiwavelength generation; Multiwavelength spectra; Polarization controllers; Semiconductor optical amplifiers